NEW SPECIES AND NEW RECORDS OF COLOMBIAN PALMS - GALEANO GLORIA; BERNAL RODRIGO (Caldasia)
Four new species of palms from Colombia, Aiphanes graminifolia, Bactris rostrata, Geonoma santanderensis and Geonoma wilsoni, are described and illustrated. Three species, Attalea cohune, A. phalerata and A. plowmanii are recorded for the first time in Colombia; the name Attalea plowmanii is a new combination based on Scheelea plowmanii. Another species, Aiphanes simplex, is recorded from the Eastern Cordillera of Colombia.